IMPROVEMENT OF THE SCIENCE OF RHYME IN TREATISES OF THE TIMURID PERIOD (American Journal of Interdisciplinary Research and Development, 2022)
In the period of Timurids, along with literature, science also rose to a high level. For poets, not only skills, but also perfect knowledge of the theory of poetry became necessary. As a result of the attention and literary influence of Timurid rulers and princes, the theoretical issues related to poetics in the existing sources were improved in harmony with the poetry of that time. The existing traditions and theoretical templates were reworked, adapted to Persian and Turkish poetry, and deficiencies were corrected. In the article, treatises on rhyme created during the Timurid period are comparatively studied.